ORIENTASI KEWIRAUSAHAAN DAN KINERJA KEUANGAN PENGEMBANGAN PRODUK BARU USAHA MIKRO DAN KECIL - Perminas Pangeran (Jurnal Riset Manajemen dan Bisnis, 2011)
The purpose of this study is toexamine the effect of entrepreneurial orientation on performance in new product development. Drawing upon a sample of 129micro and smallsized firms, multiple regression was used for testing three hypotheses. The results revealthat risk takingand proactiveness influence performance in new product development, while innovativeness show no such effect.Keywords: Innovativeness, Risk taking, Proactiveness,New Product